How do Black engineering and computing doctoral students analyze and appraise their (depleted) STEM diversity programming? - White, Devin T.; Miles, Monica L.; McGee, Ebony O.; Brockman, Amanda J. (Frontiers in Education, 2023)
Purpose Local and national U.S. programs focused on diversifying science, technology, engineering, and mathematics (STEM) in academia and industry have created academic pathways for Black Engineers. However, most STEM diversity programs in doctoral education typically end or availability significantly decreases. This absence leaves little or limited guidance during the challenging process of completing this terminal degree and seeking employment. Method We interviewed 43 Black PhD engineering and computing doctoral students, 37 discussed their experiences receiving equity-minded mentorship in a STEM diversity program, and we asked them about the value and lapsing of this programming. Results These doctoral students felt the absence of equity-minded mentoring through culturally affirming diversity programming. Often, funding for these programs has been reduced or eliminated for graduate students. National conferences, sponsored by national societies, partially filled the vacuum, offering equity-minded mentoring that affirmed STEM identities. Discussion We propose that doctoral students benefit from institutionally-maintained diversity programs that address racial disparities. These programs could provide mentoring focused on equity and based on a clear comprehension of structural racism in STEM fields. They also offer counter-narratives that challenge the underrepresentation of Black individuals in STEM.